Case report: Identification of a novel HNRNPC::RARG fusion in acute promyelocytic leukemia lacking RARA rearrangement - Ding, Wenjing; Weng, Guangyang; Wang, Zheng; Guo, Yusha; Wang, Man; Shen, Hongjie; Chen, Suning; Du, Xin; Wen, Lijun (Frontiers in Oncology, 2023)
Acute promyelocytic leukemia (APL) is a special subtype of acute myeloid leukemia (AML), 95% patients have PML-RARA fusion gene as a result of a reciprocal chromosomal translocation t(15;17)(q22; q21). The retinoic acid receptors (RARs) belong to nuclear hormone receptors which modulate the transcription of DNA elements. RARs have three isoforms: retinoic acid receptor alpha (RARA), retinoic acid receptor beta (RARB) and retinoic acid receptor gamma (RARG). In this study, we describe the experimental results of a case with HNRNPC-RARG gene transcript with morphologic and immunophenotypic features similar to APL, including bone marrow morphology and immunophenotype, which showed poor response to ATO and chemotherapy. Then the patient achieved remission under the combination of BCL-2 inhibitor (Venetoclax) and standard 7+3 chemotherapy in second induction chemotherapy. The treatment in this case demonstrates effectively response to Venetoclax, which suggested its possible role for the patient with acute promyelocytic-like leukemias (APLL).